2022
DOI: 10.1049/nbt2.12085
|View full text |Cite
|
Sign up to set email alerts
|

Diverse biotechnological applications of multifunctional titanium dioxide nanoparticles: An up‐to‐date review

Abstract: Titanium dioxide (TiO 2 ) nanoparticles (NPs) are one of the topmost widely used metallic oxide nanoparticles. Whether present in naked form or doped with metals or polymers, TiO 2 NPs perform immensely important functions. However, the alteration in size and shape by doping results in improving the physical, chemical, and biological behaviour of TiO 2 NPs. Hence, the differential effects of various TiO 2 nanostructures including nanoflakes, nanoflowers, and nanotubes in various domains of biotechnology have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 143 publications
(120 reference statements)
0
23
0
Order By: Relevance
“…ZnO could eliminate MRSA skin infection at 1875 mg/mL possibly via amino acid synthesis inhibition [ 70 ]. TiO2 NPs produce free radicals which kill MRSA [ 72 ]. Cu-doped ZnO nanorods have exhibited more potential effects than that of ZnO singly [ 73 ].…”
Section: Nanoparticle Applications To Combat Mrsamentioning
confidence: 99%
“…ZnO could eliminate MRSA skin infection at 1875 mg/mL possibly via amino acid synthesis inhibition [ 70 ]. TiO2 NPs produce free radicals which kill MRSA [ 72 ]. Cu-doped ZnO nanorods have exhibited more potential effects than that of ZnO singly [ 73 ].…”
Section: Nanoparticle Applications To Combat Mrsamentioning
confidence: 99%
“…The overuse of antibiotics can lead to the emergence of drugresistant strains, prompting the development of new antibacterial agents. Therefore, the antibacterial activity of some NPs was expected to be used in medicine (Javed, Ain et al, 2022). Metal and metal oxide NPs have been gradually recognized as the next generation of antimicrobial agents (Raghunath and Perumal 2017;Gharpure, Akash et al, 2020).…”
Section: Antibiotic Action (Microbial-related Eye Diseases)mentioning
confidence: 99%
“…ZnO-NPs are considerable antibacterial agents for contact lenses to reduce the risk of infection from wear (Shayani Rad, Sabeti et al, 2020). It was reported that titanium dioxide NPs catalyzed by UV light can effectively inhibit methicillin-resistant Staphylococcus aureus (MRSA) (Javed, Ain et al, 2022). However, the antibacterial activity is based on the photocatalytic activity of the NPs themselves, which may not work in ophthalmology.…”
Section: Antibiotic Action (Microbial-related Eye Diseases)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low solubility of hydrophobic drugs in aqueous media hampers their uptake to attain therapeutic dosage. Likewise, hydrogels based on gelatin were largely employed to generate therapeutic agents nanocarriers as a result of availability [ 12 , 13 ] in industrial waste as well as physicochemical properties and bioassimilation ability that is crucial for a wide range of medical applications [ 13 , 14 , 15 , 16 , 17 , 18 ]. Indeed, gelatin recovered from fishing by-products complies with the recommendations of the European Union to develop Circular Economy processes [ 19 ] as well as societal and religious concerns related to mammalian gelatin sources.…”
Section: Introductionmentioning
confidence: 99%